Козацтво в роботі Шарля де Пейссонеля "Історичні та географічні спостереження за варварами, які мешкають на берегах Дунаю та Чорного моря" (1756) (Observations historiques et géographiques, sur les peuples barbares qui ont habité les bords du Danube & du Pont-Euxin) - Амеліна, О. (Чорноморська минувшина, 2016)
У статті мова йде про інформацію французького дипломата Шарля (Клод-Шарля) де Пейссонеля, яка стосується території сучасної України та українського козацтва. Зазначимо, що робота Шарля де Пейссонеля “Observations historiques et géographiques, sur les peuples barbares qui ont habité les bords du Danube & du Pont-Euxin” (1756) не має перекладу з французької мови у повному обсязі. У даній статті вперше публікуються фрагмети з цієї роботи щодо теорії походження та місця локалізації українського козацтва. The article deals with the observation of the French diplomat Charles de Peyssonelya relating to the territory of Ukraine and the Ukrainian Cossacks. It should be noted that the work of Charles de Peyssonelya «Historical and geographical observation barbarians who live on the banks of the Danube and Black Sea» has no translation from the French language in its entirety. In this work, first published reflections diplomat as to the origin of the theory of localization and place of the Ukrainian Cossacks. Interest Charles de Peyssonelya was primarily associated with those regions that were strategic in nature for France. One of these regions was the territory of the Ottoman Empire. Interesting for a diplomat was the territory of the Cossacks, which directly bordered with the Tatar and Nogai ulus and entered the sphere of influence of the Crimean Khanate - vassal of the Ottoman Empire at that time. This article submitted four pieces of source «Historical and geographical observation barbarians who live on the banks of the Danube and Black Sea» which generally can be divided into two informative blocks. The first - a version of the origin of the Cossacks and the etymology of the name "Cossack", the second - information sharing Cossack groups and their localization. Focuses on the mission Peyssonelya in Crimea, during of which was written by his work «Historical and geographical observation barbarians who live on the banks of the Danube and Black Sea». Because of his work as close to the contemporary geographical and political situation. Most work «Historical and geographical observation barbaric peoples who lived on the banks of the Danube and Pontus Evksinski» 1765 is an important historical source for the history of Ukraine and the Ukrainian Cossack history in particular. We serve only fragments of these sources and note that the full translation of this work is not, and so the «Historical and geographical observation barbarians who live on the banks of the Danube and Black Sea» are important to study». В статье речь идет об информации французского дипломата Шарля (Клод-Шарля) где Пейссонеля, касающейся территории современной Украины и украинского казачества. Отметим, что работа Шарля де Пейссонеля “Observations historiques et géographiques, sur les peuples barbares qui ont habité les bords du Danube & du Pont-Euxin” не имеет перевода с французского языка в полном объеме. В данной статье впервые публикуются фрагменты из этой работы дипломата относительно теории происхождения и места локализации украинского казачества.